Analysis of the economic adaptation of Sami reindeer management. Reindeer; source of income or cultural linkage? - Labba, Niklas; Riseth, Jan Åge (Rangifer, 2007)
The aim of this partial study is to analyse how the economies of different Sami reindeer management households are structured, and how the adaptation is structured if profit maximation is a goal. Earlier research demonstrates that different regions provides various terms. Consequently there exists a different economic structure among different households. Based on a selection of households from districts /villages from a range of geographical locations, management patterns, and region size, different economic structures are searched for. Households with similar economic structures are grouped in categories. The standard deviation confirms whether the grouping in categories. Sami Reindeer Management in Norway and Sweden has during the period from 1992/93 to 2002/03 provided recognized slaughterhouses with an even quantum of meat supply. That indicates that it probably is the same set of factors that influence the slaughter quantities of both countries. The relationship between the stock value of reindeer and the commercial value of reindeer meat, with in each household, suggests whether there is an accumulation in herd size and its magnitude. The herd increment depends on the competitive situation between the households in the district/village. As a single household cannot influence wholesale price of reindeer meat, the sales quantum is the single factor that can influence total sales. The efforts to increase herd size, due to the competitive situation, prevent the household from a maximum slaughter quantum, which thereby reduce the returns from reindeer management. Common factors for the different structures are sought for. The indication is that nether sale price of reindeer meat or line of politics influence sales quantum. The Sami reindeer herding seams to be a way of life were the size of the reindeer herd is in focus.Analys av den samiska renskötselns ekonomiska tillpassning. Renen, intäktskälla eller kulturfäste?Abstract in Swedish / Sammandrag: I denna studie analyseras hur olika renskötarhushålls ...